Small business marketing kit for dummies - Schenck, Barbara Findlay (Wiley, 2012)
Harness the power of marketing and watch your business grow. Packed with tips for low-cost, high-impact campaigns, this guide is your road map to launching a dynamic marketing campaign and taking advantage of the newest technologies and avenues for outreach.